Power networks in Braga (Portugal) in late fifteenth century: town council, archbishop and the cathedral chapter relationships - Martins, Raquel de Oliveira (2015)
This article aims to characterize the existing power networks in the city of Braga (Portugal) in late fifteenth century. In this paper we analyze the relationships and power networks between the town Council, the Archbishop and the Cathedral Chapter of Braga.